Review paperThe role of substance P in rheumatoid arthritis - Lisowska, Barbara (Reumatologia/Rheumatology, 2007)
In recent years our knowledge of the role of neuropeptides in the pathogenesis of rheumatic diseases has expanded. Rheumatoid arthritis is a serious inflammatory disease of the distal joints that has a possible neurogenic component underlying its pathology. The author presents an overview of the metabolism and pharmacokinetics of substance P. The neuropeptide substance P is one possible mediator of this interaction, since it can be released into joint tissues from primary sensory nerve fibres. The peptide neurotransmitter substance P is released from the peripheral terminals of nociceptive afferent neurons and can produce physiological changes associated with acute and chronic inflammation.